The Effect of Organisational Climate on Employee Performance: The Mediating Role of Work Motivation at the Class I Banjarmasin Harbourmaster and Port Authority Office - Anovan Ashari; Misransyah Akos; Rahmadi; Septeria Noor Yuliannisa (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This study aims to analyse the influence of organisational climate on employee performance, with work motivation as a mediating variable, at the Banjarmasin Class I Harbour Master’s Office and Port Authority. The study employs a quantitative approach using a survey method and purposive sampling technique, with 48 employees as respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) via the SmartPLS version 3.29 application. The results indicate that organisational climate has a positive and significant influence on employees’ work motivation (t = 6.823; p < 0.05). Furthermore, work motivation also has a positive and significant effect on employee performance (t = 3.833; p < 0.05). In addition, organisational climate was found to have a direct effect on employee performance (t = 3.028; p < 0.05). The results of the mediation test indicate that work motivation partially mediates the relationship between organisational climate and employee performance (t = 3.464; p < 0.05). These findings confirm that improvements in employee performance are influenced not only by the creation of a conducive organisational climate, but also by the level of work motivation employees possess in carrying out their duties and responsibilities effectively.